The Invisible Burden: Diagnosing and Combatting Typhoid Fever in Asia and Africa - Pitzer, Virginia E (Clin Infect Dis, 2019)
Measuring the burden of typhoid fever and developing effective strategies to reduce it require a surveillance infrastructure that is currently lacking in many endemic countries. Recent efforts and partnerships between local and international researchers have helped to provide new data on the incidence and control of typhoid in parts of Asia and Africa. Here, we highlight examples from India, Nepal, Vietnam, Fiji, Sierra Leone, and Malawi that summarize past and present experiences with the diagnosis, treatment, and prevention of typhoid fever in different locations with endemic disease. While there is no validated road map for the elimination of typhoid, the lessons learned in studying the epidemiology and control of typhoid in these settings can provide insights to guide future disease control efforts.